Development, relative retention, and oviposition of the red flour beetle, Tribolium castaneum (herbst), on different starches - Xue, Meng (Kansas State University, 2010)
The development, relative retention, and oviposition of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), on six different types of starches, wheat flour, and wheat flour plus yeast were investigated in the laboratory. The particle size of starch and flours were different; the mean size of 90% of particles for starches ranged from 15 μm for high amylose corn starch to 58 μm for potato, whereas that of the flour was ≤ 133 μm. Larval length, head capsule width, and weight gain of T. castaneum larvae were measured every 3 d on starches, flour, and flour plus 5% (by wt) yeast diet for 30 d at 28oC, 65% r.h., and 14:10 (L:D) photoperiod. Larvae reared on flour and flour plus yeast developed normally and showed better survival compared to those reared on starches. Larvae on the starches failed to develop beyond second, and rarely, third instars. Adults of T. castaneum did not show any preference to flour over starches in dual-choice tests in circular arenas. On average, T. castaneum laid less than 3 eggs/female over a 15-d period on starches compared to 97 and 109 eggs/female on flour and flour plus yeast diet, respectively. These studies suggest that starches are poor substrates for larval survival and development. Starches were as attractive as flour to adults; however, starches do not appear to be a suitable medium for egg-laying. Both aggregation pheromone and volatiles did not trigger oviposition behavior. Experiments by moving adults between wheat starch and wheat flour and vice versa showed that feeding on wheat flour was necessary for egg-laying, indicating the absence of essential nutrients in wheat starch. On wheat flour, feeding for 0.5 d was necessary to lay eggs. Females that were starved failed to lay eggs, reinforcing that the nutrional status of females and not males was essential for egg-laying. A minimum of 4% of wheat gluten (wheat protein) elicited egg-laying on starches, although 4-5 times fewer eggs were laid in starch gluten compared with wheat flour alone. Supplementing wheat starch with 1% cholesterol, in addition, to gluten, did not result in an increase in egg-laying by T. castaneum females. These findings suggest that starches may have potential in managing development and reproduction of T. castaneum—a pest that is common and severe in food-processing facilities. Furthermore, starches can be used as a suitable substrate for studying the nutritional ecology of T. castaneum.
Keywords: Stored product entomology; Biology, Entomology (0353)